Effectiveness of flood damage mitigation measures: Empirical evidence from French flood disasters. (March 2015) - Poussin, Jennifer K.; Wouter Botzen, W.J.; Aerts, Jeroen C.J.H.
Highlights: A unique dataset of flood preparedness and damage of 885 households is collected. Empirical evidence of damage avoided by flood damage mitigation measures is offered. These measures are evaluated for three regions with different flooding conditions. Flood damage mitigation measures are ranked according to their cost-effectiveness. General lessons for flood risk management policy are discussed. Abstract: Recent destructive flood events and projected increases in flood risks as a result of climate change in many regions around the world demonstrate the importance of improving flood risk management. Flood-proofing of buildings is often advocated as an effective strategy for limiting damage caused by floods. However, few empirical studies have estimated the damage that can be avoided by implementing such flood damage mitigation measures. This study estimates potential damage savings and the cost-effectiveness of specific flood damage mitigation measures that were implemented by households during major flood events in France. For this purpose, data about flood damage experienced and household flood preparedness were collected using a survey of 885 French households in three flood-prone regions that face different flood hazards. Four main conclusions can be drawn from this study. First, using regression analysis results in improved estimates of the effectiveness of mitigation measures than methods used by earlier studies that compare mean damage suffered between households who have, and who have not, taken these measures. Second, this study has provided empirical insights showing that some mitigation measures can substantially reduce damage during floods. Third, the effectiveness of the mitigation measures is very regional dependent, which can be explained by the different characteristics of the flood hazard in our sample areas that experience either slow onset river flooding or more rapid flash and coastal flooding. Fourth, the cost-efficiency of the flood damage mitigation measures depends strongly on the flood probability faced by households.